Evaluation of the High School Students’ Perceived Social Support Scale (KraS-DS) Using the Rasch Model - Indriyana Rachmawati; Widya Juwita Sari; Sesya Dias Mumpuni; Restu Dwi Ariyanto; Indriyana Rachmawati; Widya Juwita Sari; Sesya Dias Mumpuni; Restu Dwi Ariyanto (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2026)
Perceived social support is needed by adolescents to prevent mental health problems and achieve the expected well-being. The absence of social support, whether from parents, teachers, and friends, has an impact on individual feelings and emotions. The urgency of perceived social support for adolescent life requires a valid and reliable instrument to measure the condition of adolescent social support. The purpose of this study was to produce a valid and reliable social support scale for high school students (KraS-DS) using the Rasch model. The quantitative research method used the Rasch Model to evaluate the KraS-DS instrument to ensure its validity and reliability. Participants were 212 adolescents attending high schools in Karanganyar District. Data were collected through a survey using a paper and pencil test. The results of the analysis showed that (1) the person reliability and item reliability of the social support scale can be said to be good, meaning that the items and responses from respondents were quite consistent; (2) item number X4 is the item that has the highest level of difficulty or is difficult to agree with; (3) the function of the rating scale on the social support scale has worked well; and (4) the item discrimination power on the social support scale can be said to be good, even though items 7 and 8 do not fit the Rasch model.